Relationship between diagnosis of conus arteriosus malformation and genetic diagnosis results in fetal cardiac axis abnormalities by echocardiography during middle pregnancy - Yang, Lin; Cai, Yuting; Chen, Huie; Ke, Linfang; Wu, Shufen (Frontiers in Cardiovascular Medicine, 2024)
Objective To explore the clinical value of echocardiography in detecting fetal cardiac axis abnormalities during middle pregnancy for diagnosing conus arteriosus malformation, and to compare and analyze the genetic diagnosis results, in order to provide evidence for clinical diagnosis and intervention. Methods Four hundred twenty-one fetuses with conus arteriosus malformation from January 2020 to October 2023 were included as the conus arteriosus malformation group, and 917 healthy fetuses (all single fetuses) matched at the same gestational age were selected as the healthy group. Results There was no significant difference in gestational weeks between two groups (P > 0.05). The age of pregnant women in conus arteriosus malformation group was lower compared to healthy group (P < 0.05), and the fetal cardiac axis in conus arteriosus malformation group was significantly higher compared to healthy group (P < 0.05). Among the fetuses with conus arteriosus malformation, tetralogy of Fallot (TOF), transposition of the great arteries (TGA) and double outlet right ventricle (DORV) had the highest proportions, accounting for 38.00%, 18.29% and 17.58%, respectively. Among all types of conus arteriosus malformations, atresia pulmonary valve syndrome associated with TOF, persistent truncus arteriosus and DORV exhibited higher proportions of fetal cardiac axis abnormalities, at 75.00%, 36.84% and 27.03%, respectively, while TGA and interrupted aortic arch associated with B-type interruption had lower proportions of fetal cardiac axis abnormalities, at 2.60% and 4.55%, respectively. Genetic testing was conducted on 73 cases (17.34%) of fetuses with conus arteriosus malformation in this study. Among them, fetal cardiac axis abnormalities were considered positive for genetic results due to factors such as aneuploidy, copy number abnormalities, and single-gene pathogenicity. A total of 31 cases tested positive for genetic anomalies, with a positive rate of approximately 42.47%. Conclusion In the middle pregnancy, the fetal cardiac axis in cases of conus arteriosus malformation was significantly higher than in normal fetuses. Moreover, there were variations in fetal cardiac axis among different types of conus arteriosus malformations, and these differences were notably associated with genetic diagnostic results.